The Academic as Comedian: Humour in Michael Frayn’s The Trick of It - Isabel Berzal Ayuso (Polish Journal of English Studies, 2019)
Michael Frayn’s comic novel The Trick of It (1989) explores the rela-tionship between academia and creative writing and the derivative, secondary nature of literary research. Through its main academic character and only narra-tor, Frayn’s text recurrently identifies the role of a scholar with the role of a hu-mourist in that both share a higher-than-average degree of self-awareness and detailed knowledge about the world. Through such identification, present in the novel both implicitly and explicitly, The Trick of It underscores the secondary and limited nature of academic work, yet it also gives an ultimately positive image of it. By pairing academic research and humour, Frayn’s novel shows that literary scholarship is as a discipline that, much like humour, can enlarge our understanding and enjoyment of whatever it refers to.